2018
DOI: 10.1177/0003489418787833
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ-Mediated p21 Induction in Aerodigestive Preneoplastic Cell Lines

Abstract: We conclude the PPARγ activator, pioglitazone, can activate p21, which is associated with decreased proliferation in 2 aerodigestive preneoplastic cell lines. In addition, the p21 gene may be a potential hypothesis-driven biomarker in translational studies of pioglitazone as a chemoprevention agent for aerodigestive cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
4
1
Order By: Relevance
“…To our knowledge, this is the first epidemiological study using population‐based case‐control methodology to assess the association between pioglitazone use among patients with type 2 DM and the subsequent occurrence of HNC. Our findings contradict previous laboratory research findings, two phase II clinical trials, and a prospective cohort study, which suggested a chemoprotective effect of pioglitazone in oral/head and neck cancers. Notably our study not only showed no protective effect but, on the contrary, shows increased odds of oral cavity and HNC cancer with pioglitazone use.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, this is the first epidemiological study using population‐based case‐control methodology to assess the association between pioglitazone use among patients with type 2 DM and the subsequent occurrence of HNC. Our findings contradict previous laboratory research findings, two phase II clinical trials, and a prospective cohort study, which suggested a chemoprotective effect of pioglitazone in oral/head and neck cancers. Notably our study not only showed no protective effect but, on the contrary, shows increased odds of oral cavity and HNC cancer with pioglitazone use.…”
Section: Discussioncontrasting
confidence: 94%
“…PPARγ agonists as a chemoprevention agent for HNC have been established in many laboratory studies . There remains a paucity of human clinical studies, specifically whether PPARγ agonists such as pioglitazone used in patients with type 2 DM could be preventive against HNC .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Miller et al demonstrated that the induction of p21 is rapid and does not last long. In their study, the strongest increase in p21 protein and transcript levels was observed after 6 h of incubation with PPAR-γ activator; however, after 24 h, this effect diminished [51]. As our shortest incubation period with CLA was 24 h, it is possible that we could omit any possible changes in CDKN1A mRNA level.…”
Section: Cell Line/genementioning
confidence: 80%
“…Despite limited studies that have has been conducted on the PPARs, they have been linked to various conditions such as the levels of lipoprotein, cardiovascular disease, diabetes, obesity, and malignancies [27]. PPARs exposed an active role in glucose and lipid metabolism, and the regular functioning of the adipose cells [28].…”
Section: Discussionmentioning
confidence: 99%